Iron(III)-catalyzed activation of C(sp2)-H and C(sp3)-H bonds for H/D exchange of arenes - Chang Zheng; Yu Tang; Biao Yu (Nature Communications)
Abstract Iron-catalyzed C-H activation reactions via organometallic Fe-C intermediates have been extensively studied during the past two decades. One issue remains to be clarified is whether iron(III) salts containing weakly coordinating anions could directly activate C(sp2)-H or C(sp3)-H bonds without the assistance of a directing group. Herein, we report our finding that iron(III) salts containing weakly coordinating anions can indeed be effective catalyst for the direct activation of C(sp2)-H and C(sp3)-H bonds under weakly coordinating environment. This mechanism could be extended to other types of first-row transition metal complexes such as Co(II), Ni(II), and Cu(II). Thus, an iron(III) catalyzed H/D exchange reaction for aromatic C(sp2)-H bonds and the corresponding β-C(sp3)-H bonds of the alkyl substituents is developed, unlocking an easy access to the valuable deuterated aromatic products from feedstock chemicals.